Günümüz Türkçesiyle Evliyâ Çelebi seyahatnâmesi : Akkirman, Belgrad, Gelibolu, Manastır, Özü, Saraybosna, Slovenya, Tokat, Üsküp, 5. kitap, 2. cilt - Evliyâ Çelebi, 1611-1684? (İstanbul)
xx s., 417-899